IMPLEMENTATION OF GOVERNMENT REGULATION NUMBER 19 OF 2022 CONCERNING TASK OF ASSISTANCE TO CONTRIBUTION TO VILLAGE GOVERNMENT SUKADAME IN CARRYING OUT THE VOTING PROPERTY TAX - Tanaya Anas Tasya Simangunsong; Agus Anjar; Maya Jannah (Jurnal Ilmiah Advokasi, 2024)
The aim of this research is to describe the implementation of Government Regulation Number 19 of 2022 concerning assistance tasks in the Suka Dame Village Government, Silangkitang District in terms of collecting Land and Building Tax (PBB). The lack of progress at the regional level regarding the implementation of PP Number 19 of 2022 indicates that assistance tasks at the village level have not gone as expected. The assistance task is a mandate from the Central Government to the Regions to carry out according to what has been mandated in the law. The problem obtained in this research is whether the Suka Dame Village Government has implemented Government Regulation Number 19 of 2022 properly in terms of collecting Land and Building Tax. In order to find answers to the problem formulation, the researcher carried out a research method using a qualitative approach using research instruments of observation, interviews and documentation by appointing 4 key informants. The results of the research show that some people are less active in carrying out their obligations as citizens, out of a total population of 2923 people, 1806 people actively pay land and building tax. This gives an indication that the assistance tasks as stated in PP Number 19 of 2022 in Suka Dame Village have not gone well.Keywords: Implementation, Assistance Duties, Village Government, land and building taxes